Donor profile and trends of eye donation in Central India - Jat, Neha Singh (International Journal of Clinical and Experimental Ophthalmology, 2021)
Background: The present study was conducted to study the donor profile and to assess the trends of cornea donation. Methodology: This was conducted as a hospital based cross sectional study at a tertiary care centre in Central India for a period of 5 years. Data was retrieved from 70 patients from eye bank who filled form of eye donation at Eye bank of our institution. Sociodemographic profile of donors, cause of death and time since death was recorded. Source of information regarding corneal donation and reason for not willing to donate the cornea for research purpose was recorded from the filled form. Further cornea enucleated were subjected to serology and their utilization for various purposes were recorded in questionnaire. Results: The present study retrieved data from a total of 70 donor forms with mean age of 65.84 ± 18.4 years. Cornea obtained from younger patients were mainly utilized for corneal transplantation whereas that from elderly age group > 60 years were mainly utilized for research/training purpose and the observed difference was statistically significant (p < 0.01). The corneas retrieved and utilized immediately after death were significantly used for optical or therapeutic purposes (p < 0.05). Conclusion: The present highlights the donor profile and trends of corneal donation at the tertiary care facility of Central India. It was observed that though the younger population and older population both are aware regarding corneal donation but still they are less aware on purpose for which cornea can be utilized. Quality of donor cornea is better when death to enucleation time interval was less.